Foot-and-Mouth Disease Virus Serotype SAT 3 in Long-Horned Ankole Calf, Uganda - Tefula Dhikusooka, Moses; Tjørnehøj, Kirsten; Ayebazibwe, Chrisostom; Namatovu, Alice; Ruhweza, Simon; Redlef Siegismund, Hans; Nabalayo Wekesa, Sabenzia; Normann, Preben; Belsham, Graham J. (Emerging Infectious Diseases, 2015)
Foot-and-mouth disease (FMD) remains one of the most economically important diseases of livestock, costing ≈US $10 billion annually (1). Outbreaks occur in many countries, and normally disease-free countries can incur huge costs after incursions (e.g., the United Kingdom in 2001). The disease results from infection with FMD virus (FMDV, the prototypic aphthovirus within the Picornaviridae family) (2). Seven serotypes of FMDV are known; serotypes O and A are widely distributed, and the Southern African Territories (SAT) serotypes (1, 2, and 3) usually are restricted to Africa. Serotype Asia 1 has never circulated within Africa; serotype C has not been identified anywhere since 2005 (2,3). SAT 3 FMDV is the least well–characterized serotype; the most recent incidence of SAT 3 reported by the FMD World Reference Laboratory (Pirbright Institute, Woking, UK) was in buffalo within the Kruger National Park (South Africa) in 2006. In contrast, SAT 1 and SAT 2 FMDVs are much more common; a major incursion of SAT 2 into the Middle East occurred in 2012 (4), and outbreaks caused by these serotypes have occurred in many African countries (http://www.wrlfmd.org/fmd_ genotyping/2013.htm). In Uganda, FMD is endemic, and serotypes O and SAT 2 are the most common. In Uganda, SAT 3 FMDV was most recently identified in 1997 in buffalo in the Queen Elizabeth National Park (QENP) (5). SAT 1 and SAT 2 viruses were isolated from buffalo in QENP in 2006, and serologic test results indicated the presence of antibodies against SAT 3 virus; however, because cross-reactivity between serotypes occurs in these assays, this finding was not conclusive
Keywords: Foot-and-Mouth Disease Virus Serotype SAT 3; Long-Horned Ankole Calf